2018
DOI: 10.1371/journal.pone.0202563
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antidiabetic drugs added to sulfonylurea monotherapy in patients with type 2 diabetes mellitus: A network meta-analysis

Abstract: AimsThis study aimed to investigate the efficacy and safety of dual therapy comprising sulfonylurea (SU) plus antidiabetic drugs for the treatment of type 2 diabetes mellitus (T2DM).MethodsWe searched the PubMed, Cochrane library, and Embase databases for randomized clinical trials (≥24 weeks) published up to December 28, 2017. Subsequently, we conducted pairwise and network meta-analyses to calculate the odds ratios (ORs) and mean differences (MDs) with 95% confidence intervals (CIs) of the outcomes.ResultsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
1
7
0
2
Order By: Relevance
“…A recent network meta-analysis of different AHA classes added to SU monotherapy concluded that SGLT2 inhibitors have distinct advantages over other AHA classes, as they not only significantly improve glycemic control but they may also reduce the risk of hypoglycemia and BW [39]. In both the primary and post-hoc analyses of the VERTIS CV substudy reported here, the mean reductions in BW from baseline with both doses of ertugliflozin were commensurate with the reduction predicted in that meta-analysis.…”
Section: Discussionsupporting
confidence: 73%
“…A recent network meta-analysis of different AHA classes added to SU monotherapy concluded that SGLT2 inhibitors have distinct advantages over other AHA classes, as they not only significantly improve glycemic control but they may also reduce the risk of hypoglycemia and BW [39]. In both the primary and post-hoc analyses of the VERTIS CV substudy reported here, the mean reductions in BW from baseline with both doses of ertugliflozin were commensurate with the reduction predicted in that meta-analysis.…”
Section: Discussionsupporting
confidence: 73%
“…Our results were consistent with those of a meta-analysis in which the use of metformin increased the risk of hypoglycemia, resulting in a 1.5-times higher risk in the SU and metformin group than in the SU monotherapy group. 40 The risk of hypoglycemia was 1.6-fold higher in the group receiving combination therapy of SUs, DPP-4i, and metformin than in the SUs and DPP-4i groups. These results are probably due to the combined effect of increase in insulin sensitivity by metformin and stimulation of insulin secretion by SUs, because metformin alone does not increase the risk of hypoglycemia significantly.…”
Section: Discussionmentioning
confidence: 92%
“…41 A meta-analysis also showed that the combination of SUs and metformin resulted in a 2.0-fold higher risk of hypoglycemia than SUs and DPP-4i. 40 Chloramphenicol, isoniazid, linezolid, and prothionamide showed a grouped aOR of 5.48 (95% CI 2.19-13.68). However, the sample size was small, and further studies are needed.…”
Section: Discussionmentioning
confidence: 94%
“…We had expected weight to be an important discriminating factor in the choice of anti-diabetes treatment as it significantly influences glycemic control and macrovascular complications. It is also well known that overweight and obese patients are more likely to be affected by T2DM, with the odds ratio increasing from the lowest BMI category to the highest [ 1 , 4 , 16 19 ].…”
Section: Discussionmentioning
confidence: 99%